LINE FOLLOWER ROBOT BERBASISKAN MIKROKONTROLER ATMEL 16 - Yani Prabowo (Universitas Budi Luhur, 2011)
Robotics is continuos growing unconscious man had begun to rely on robots to help in a variety of jobs, especially jobs that are routine and very dangerous. This study is an exploration and development of robotics by using the ATMEL microcontroller 16, the task of the robot is designed to follow the track by reading sensors and duties in accordance with a given program. This robot moves automatically and runs follow existing line on the field or by tracking and carring objects and put them together. This robot uses one microcontroller ATMEL 16 that can be programmed within their command. Microcontroller in used for tracking a white line at 5 cm, where the sensor tracking used 6 LDR sensor. This microcoltroller is used for picking and flower Krathong and shift the body. Tracking sensors used are LDR sensor reading the ADC, the analog voltage from the sensor where it will be converted into a digital voltage. Atmega16 microcontroller it self al ready has an internal ADC, and can be actived through the program.Keyword : Microcontroller, Robotics, Sensor Tracking, Embeded Program